The P wave dispersion—one pixel, one millisecond - Zawadzki, Jacek; Zawadzki, Grzegorz; Radziejewska, Jadwiga; Wolff, Peter-Stephan; Sławuta, Agnieszka; Gajek, Jacek (Reviews in cardiovascular medicine, 2021)
The electrophysiological activity of the heart is recorded and presented in form of electrocardiogram (ECG). In 1998 the concept of P wave dispersion as the risk factor for atrial fibrillation (AF) recurrence was introduced. It was calculated as the difference between the longest and the shortest P wave. The aim of our study is to prove that the P wave dispersion is an artifact of low accuracy in P wave measurement. The study included 186 patients (78M 108F) aged 59.7 ± 12.9 years, undergoing various electrophysiological procedures. The P wave was measured twice: first, at the paper speed of 50 mm/s, enhancement 8× (standard – imprecise) and the second time at 200 mm/s, 64–256× (precise). The imprecise measurement method resulted in different duration of all P wave parameters in comparison with precise measurement. The difference between Δ P max and Δ P min indicated a higher value for the latter parameter. It was indicated that the imprecise P wave dispersion value correlated most significantly with the maximal P wave duration, which was measured in a similar way. In contrast with the imprecise measurement method, the minimal and maximal durations of the P waves, being measured accurately, were almost identical. Using precise methodology, the P wave dispersion reaches negligible values and tends to zero. The measurements of the P wave have to be precise to assure the highest scientific and medical sincerity. The highest clinical value is related to the P wave duration.